2013
DOI: 10.1139/cjfas-2012-0298
|View full text |Cite
|
Sign up to set email alerts
|

How do the organic and mineral fractions drive the opacity of fish otoliths? Insights using Raman microspectrometry

Abstract: International audienceWe investigated the relationships between the opacity and the physico-chemical characteristics of fish otoliths and more specifically their aragonite and organic fractions. The analysis of these two fractions on otolith macrostructures was performed using Raman microspectrometry on both translucent and opaque zones of otoliths of pollock (Pollachius virens) and European hake (Merluccius merluccius). The magnitude of the Raman signatures of the aragonite and organic fractions were strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Like our in vivo profiling results, high‐resolution ex vivo mapping showed that the corals and fish otolith are composed entirely of aragonite, whereas the foraminifer and coralline alga are entirely calcitic, except for minor aragonite contamination or infilling in the coralline alga. The banding of ν 1 peak intensity in the fish otolith may be due to differing proportions of organics and aragonite crystals (Jolivet, Bardeau, Fablet, Paulet, & Pontual, ). Conversely, micro‐banding patterns in the aragonitic corals are likely caused by variations in calcifying fluid Ω Ar , which could also explain the Mg/Ca banding observed here (Figure c,d) and described previously (Meibom et al, ) because aragonite Mg/Ca increases with Ω Ar or crystal growth rate (AlKhatib & Eisenhauer, ; DeCarlo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Like our in vivo profiling results, high‐resolution ex vivo mapping showed that the corals and fish otolith are composed entirely of aragonite, whereas the foraminifer and coralline alga are entirely calcitic, except for minor aragonite contamination or infilling in the coralline alga. The banding of ν 1 peak intensity in the fish otolith may be due to differing proportions of organics and aragonite crystals (Jolivet, Bardeau, Fablet, Paulet, & Pontual, ). Conversely, micro‐banding patterns in the aragonitic corals are likely caused by variations in calcifying fluid Ω Ar , which could also explain the Mg/Ca banding observed here (Figure c,d) and described previously (Meibom et al, ) because aragonite Mg/Ca increases with Ω Ar or crystal growth rate (AlKhatib & Eisenhauer, ; DeCarlo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our model assumes a homogeneous dispersion of organic and mineral fractions, which is known to be a simplification (Dauphin and Dufour, 2008). Variation in organic content with circadian rhythm has been long described in otoliths, although quantitative data remains sparse (Jolivet et al, 2013a). The true ultrastructure of otoliths includes nanometric organic envelopes and variation of organic/mineral ratios within growth increments, which are only beginning to be described and are very difficult to accurately model.…”
Section: Quantification Processmentioning
confidence: 99%
“…Raman spectra of fish otoliths have shown higher organic signals in dark bands; however, these were signals from proteinaceous material and not from pigments. [24] It has been speculated that pigments are modified from food, and therefore, different colors and pigments found in the same species of mollusk may be due to different habitats. [12] Although the source of pigments in larval shells is unknown, if larvae incorporate pigments via algal food (metabolic) sources, pigments from the early PDI shell may differ from those in the later shell because the larva does not feed during PDI formation.…”
Section: Introductionmentioning
confidence: 99%